PENGARUH PENDEKATAN CTL DENGAN SOAL OPEN ENDED TERHADAP KEMAMPUAN BERPIKIR KREATIF MAHASISWA - Puput Wahyu Hidayat; ABDULAH - (LP3M Universitas Muhammadiyah Muara Bungo, 2018)
The purpose of the study was to analyze the effect contextual teaching and learning approach with open ended question toward creative thinking ability at PGSD STKIP Muhammadiyah Muara Bungo. The Research concept used quantitative research, with pretest-posttest non-equivalent group design. This Research population include all members od second semester student which has 4 classes. Meanwhile, two choosen classes made for an example of Research it was Class B and C. Test instruments were used to describe the creative thinking ability question. The founding of the research showed that; 1) The data analysis (average score) shown that student’s creative thinking ability for ekperimen class in range very high level, posttest average score is 80,93; 2) for control class in range high level, posttsest average score is 78,40. 3) Contextual teaching and learning approach with open ended question is better than conventional approach toward creative thinking ability.